Association between Socioeconomic Position of the Family and Adolescent Obesity in Germany-Analysis of the Mediating Role of Familial Determinants. - Blume, Miriam; Schienkiewitz, Anja; Wollgast, Lina; Hoffmann, Stephanie; Sander, Lydia; Spallek, Jacob; Herr, Raphael M.; Moor, Irene; Pischke, Claudia R.; Iashchenko, Iryna; Hövener, Claudia; Rattay, Petra (Journal of Obesity, 2024)
BACKGROUND: Obesity's negative impact on young people's health has long been known. The family and its socioeconomic position (SEP) are key determinants in adolescent obesity. However, understanding which familial determinants explain the association remains limited. METHOD: The analyses are based on data from the "German Health Interview and Examination Survey for Children and Adolescents" (KiGGS) (1,384 females and 1,332 males aged 11 to 17 years). Logistic regression models explored how familial determinants (family stress, family cohesion, parental smoking, parental sporting activity, and parental overweight) mediated the association between family SEP (parental education, occupational status, and household income) and adolescent obesity. RESULTS: Significant total effects for the associations between family SEP in childhood and adolescent obesity were found. Splitting the total effect of the family SEP on obesity into direct and indirect effects, all direct effects turned out to be significant. However, all associations involved also indirect effects of familial determinants, except for household income for female adolescents. Parental smoking and overweight were the most relevant mediators for males and females. For male adolescents, parental sporting activity additionally mediated the association between SEP and obesity. CONCLUSION: A low SEP in childhood was associated with adolescent obesity. Parental health and health behaviors partly explained the association. For increasing health equality in adolescent health, the consideration of parental health behavior in the planning and implementation of health promotion programs seem to be important.
EVALuna2:575114